Morphological and functional characterization of human induced pluripotent stem cell‐derived neurons (iCell Neurons) in defined culture systems. (11th September 2015) - Berry, Bonnie J.; Akanda, Nesar; Smith, Alec S.T.; Long, Christopher J.; Schnepper, Mark T.; Guo, Xiufang; Hickman, James J.
Abstract : Pre‐clinical testing of drug candidates in animal models is expensive, time‐consuming, and often fails to predict drug effects in humans. Industry and academia alike are working to build human‐based in vitro test beds and advanced high throughput screening systems to improve the translation of preclinical results to human drug trials. Human neurons derived from induced pluripotent stems cells (hiPSCs) are readily available for use within these test‐beds and high throughput screens, but there remains a need to robustly evaluate cellular behavior prior to their incorporation in such systems. This study reports on the characterization of one source of commercially available hiPSC‐derived neurons, iCell ® Neurons, for their long‐term viability and functional performance to assess their suitability for integration within advanced in vitro platforms. The purity, morphology, survival, identity, and functional maturation of the cells utilizing different culture substrates and medium combinations were evaluated over 28 days in vitro (DIV). Patch‐clamp electrophysiological data demonstrated increased capacity for repetitive firing of action potentials across all culture conditions. Significant differences in cellular maturity, morphology, and functional performance were observed in the different conditions, highlighting the importance of evaluating different surface types and growth medium compositions for application in specific in vitro protocols. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:1613–1622, 2015